Donor‐Transmitted HTLV‐1‐Associated Myelopathy in a Kidney Transplant Recipient—Case Report and Literature Review. Issue 10 (19th August 2014) - Ramanan, P.; Deziel, P. J.; Norby, S. M.; Yao, J. D.; Garza, I.; Razonable, R. R.
<x xml:space="preserve">Abstract</x> Clinical disease due to human T cell lymphotropic virus type 1 (HTLV‐1), a retrovirus endemic in certain regions of the world, is rarely reported after solid organ transplantation. In 2009, universal deceased donor organ screening for HTLV‐1 was discontinued in the United States. We report the first case of donor‐derived HTLV‐1‐associated myelopathy in a kidney transplant recipient from the United States. The patient, who was HTLV‐1‐seronegative prior to transplantation, likely acquired HTLV‐1 infection from a seropositive organ donor. In this era when screening of donors and recipients for HTLV infection is not mandatory, clinicians should be vigilant in recognizing the risk and potential occurrence of this donor‐derived infection in recipients with epidemiologic exposures.